Transformational Leadership and Organizational Agility in the Era of Industry 4.0 - Sasmita, Yuliana; Aditya, Kevin; Purnamasari, Sari; Nor, Nur Amalina Mohd (Journal of Economics and Management, 2025)
This study examines the role of transformational leadership in enhancing organizational agility within the context of Industry 4.0. As organizations face rapidly changing technological landscapes, agility becomes a critical capability for sustaining competitiveness. Using a quantitative approach, data were collected through a survey of 210 mid-level managers and supervisors across manufacturing and service industries in Indonesia. The study employs Structural Equation Modeling (SEM) to assess the relationship between four dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration and organizational agility. Results indicate that all dimensions of transformational leadership significantly and positively affect organizational agility, with intellectual stimulation having the strongest influence. The findings suggest that transformational leaders enable organizations to navigate uncertainty, adapt to change, and innovate continuously. This research contributes to the growing literature on agile leadership in digital transformation contexts and provides actionable insights for managers leading in dynamic environments.